Concept analysis of impressionability among adolescents and young adults - (:unkn) unknown (My University, 2018)
Aim: To report a concept analysis of impressionability among adolescents and young adults. Background: Adolescence and young adulthood are critical periods to establish health behaviour. Environmental determinants are associated with youth health risk behaviours. These populations are impressionable to a range of social and physical environmental factors. Design: Concept analysis. Methods: We selected 17 studies to review from Psych INFO, ERIC, MEDLINE, and Google Scholar as well as the University of Virginia library. We did not apply date limits. We included search terms: “adolescent”; “youth”; “young adult”; “impressionability”; and “impressionable.” Results: The defining attributes of impressionability among youths were a state where: (a) one is able to be susceptible to external stimuli; (b) one is incapable of reasonable judgement; and (c) one has a changeability to accept or modify one’s attitude and behaviour. We identified antecedents, consequences, and cases of impressionability.
Keywords: adolescent; commercial; concept analysis; impressionability; or not‐for‐profit sectors; youth